Samarkand State University of Architecture and Construction (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In construction, coatings in the form of solid single-span floorings from spatial blocks with a cylindrical shell are successfully used. The cylindrical shell in the space block has a small rise. Therefore, the forces acting in its middle surface are close in value to their projections on the base of the shell.